The Emergence of Coxsackievirus A16 Associated with HFMD Colloquially Termed ‘Tomato Flu’ in India 2022: A Detailed Virological Inspection - Sougata Rajak; Saanya Chaturvedi (International Journal of Vaccines, 2024)
As the world battles the COVID-19 pandemic and grapples with a concerning spike in monkeypox cases, India has encountered another viral illness dubbed "Tomato Flu." Tomato Flu is a viral disease caused by coxsackievirus A16, which is a highly infectious illness affecting children under 10 years old.. Enterovirus A71, CV-A16, CVA6, and echoviruses are the causes of what is also referred to as hand, foot, and mouth disease (HFMD). The epidemiological attributes of this disease have been documented, and the replication process of CV-A16 is closely related to that of enterovirus infection. The main avenue of viral transmission is through close interaction with infected children. Symptoms include blisters beneath the palms and feet, rashes throughout the body, fever, dehydration, and joint swelling. Prevention is crucial, including hydration, avoidance of touching blisters, proper isolation, hygiene maintenance, and frequent washing or sanitizing. General treatment can be applied to both Tomato Flu and HFMD manifestations. Currently, there is no available tomato flu vaccine; however, the CV-A16 vaccine from Lactococcus lactis has been developed as an oral vaccine to prevent CV-A16. An inactivated vaccine was also produced using the CVA16-393 strain. However, further investigation is required to ascertain its applicability in this context.
Keywords: Coxsackievirus A16; Enterovirus 71; HFMD; Inactivated vaccine; Lactococcus lactis; Oral vaccine; Tomato flu; epidemiology